Selting, Margret, and Dagmar Barth-Weingarten, eds. New Perspectives in Interactional Linguistic Research. Amsterdam: John Benjamins, 2024. 428 pp. (ISBN: 978-90-2724-691-2) (Rilce. Revista de Filología Hispánica, 2025)
Book Review